The effect of Mg concentration on the resistance of PVD Zn-Mg coatings to corrosion driven organic coating delamination. (November 2015) - Davies, J.L.; Glover, C.F.; Van de Langkruis, J.; Zoestbergen, E.; Williams, G.
Highlights: Thin PVD Zn–Mg films of varying composition were deposited on iron substrates. Corrosion-driven delamination was investigated on model organic-coated samples. In-situ scanning Kelvin probe data was used to quantify rates of underfilm corrosion. Cathodic disbondment was stopped at Mg compositions of 10 wt% and higher. Coating failure by anodic disbondment occurred when the Mg content exceeded 10 wt%. Abstract: Zn–Mg PVD coatings applied to steel substrates are investigated with respect to their resistance to corrosion-driven organic coating delamination by both cathodic and anodic mechanisms. An in-situ scanning Kelvin probe is employed to quantify delamination rates on model polyvinyl butyral coated surfaces and determine the underfilm potentials associated with the delamination corrosion cell. Measurable rates of cathodic disbondment are observed at Mg compositions of ≤5% w/w, but all other Zn–Mg coatings in the range 10–25% w/w resist delamination for periods of up to 48 h. However, Mg compositions of ≥12% w/w produce a susceptibility to coating failure by anodic undermining.